TiO2 nanotube coating on stainless steel 304 for biomedical applications - Zalnezhad, E.; Harnouda, A.M.S.; Faraji, G.; Sharnshirband, S. (Elsevier Sc. Ltd., 2015)
The present study describes the anodic growth of TiO2 nanotube thin layer on stainless steel 304 in ethylene glycol/water/ammonium fluoride electrolyte. In this regard, pure titanium was coated on stainless steel 304 substrates by a physical vapor deposition magnetron sputtering (PVDMS) technique. The adhesion strength of the coating to the substrate was investigated. TiO2 nanotubes were generated on the top of the Ti coated substrates by means of anodization technique at a 25 V potential and times of 20, 40, and 60 min in an ammonium fluoride electrolyte solution. The anodized Ti-coated samples were heat-treated at 280 degrees C, 430 degrees C and 620 degrees C in a N-2 gas furnace to attain diverse phases. The mechanical properties of TiO2 nanotube arrays coated substrate were explored by a nanoindentation apparatus. The results illustrate that the Young's modulus and surface hardness of TiO2 nanotube-coated substrates are increased with increasing annealing temperatures (280 degrees C, 430 degrees C and 620 degrees C). The scratch test results show that heat treatment at 430 degrees C and 620 degrees C can improve the adhesion strength of Ti/TiO2 coated samples by up to 2860 and 3140 mN, respectively. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.